Role of interpretation in management: a case study of the protected area system in Nepal - Thapa, Barna Bahadur (Banko Janakari, 2009)
Interpretation, as an educational activity along with enjoyment promised to increase awareness, appreciation and understanding of the protected areas. Though relatively new concept to Nepal it is widely used in western countries as a tool of park management. Closely related to environmental education or conservation education in our context it also helps to manage natural resources and human resources. This study describes the role of interpretation in park management examining the interpretation theory using Nepal as a case study. Questionnaire survey was used to obtain the data and the results indicate that there is strong relationship between interpretation and park management. All of the survey groups reported positive links with park management. This study identifies the problems existing and improvements to be made in the interpretive facilities, training and equipment in relation to protected area management in Nepal. Key words: Interpretation, Conservation education, parks and protected areas, park management, Nepal doi: 10.3126/banko.v17i2.2154 Banko Janakari, Vol. 17, No. 2, 40-44